Bioactive polymersomes self-assembled from amphiphilic.PPO-glycopolypeptides: synthesis, characterization, and dual-dye encapsulation - Das, Soumen; Sharma, Dharmendar Kumar; Chakrabarty, Suman; Chowdhury, Arindam; Sen Gupta, Sayam (Langmuir, 2015)
Glycopolypeptide-based polymersomes have promising applications as vehicles for targeted drug delivery because they are capable of encapsulating different pharmaceuticals of diverse polarity as well as interacting with specific cell surfaces due to their hollow structural morphology and bioactive surfaces. We have synthesized glycopolypeptide-b-poly(propylene oxide) by ROP of glyco-N-carboxyanhydride (NCA) using the hydrophobic amine-terminated poly(propylene oxide) (PPO) as the initiator. This block copolymer is composed of an FDA-approved PPO hydrophobic block in conjugation with hydrophilic glycopolypeptides which are expected to be biocompatible. We demonstrate the formation of glycopolypeptide-based polymersomes from the self-assembly of glycopolypeptide-b-poly(propylene oxide) in which the presence of an ordered helical glycopolypeptide segment is required for their self-assembly into spherical nanoscale (similar to 50 nm) polymersomes. The polymersomes were characterized in detail using a variety of techniques such as TEM, AFM, cryo-SEM, and light-scattering measurements. As a model for drugs, both hydrophobic (RBOE) and hydrophilic (calcein) dyes have been incorporated within the polymersomes from solution. To substantiate the simultaneous entrapment of the two dyes, spectrally resolved fluorescence microscopy was performed on the glycopeptide polymersomes cast on a glass substrate. We show that it is possible to visualize individual nanoscale polymersomes and effectively probe the dyes colocalization and energy-transfer behaviors therein as well as investigate the variation in dual-dye encapsulation over a large number of single polymersomes. Finally, we show that the galactose moieties present on the surface can specifically recognize lectin RCA(120), which reveals that the polymersomes surface is indeed biologically active.

Biopolymer/glycopolypeptide-blended scaffolds: synthesis, characterization and cellular interactions - Dhaware, Vinita; Diaz, David Diaz; Sen Gupta, Sayam (Chemistry-An Asian Journal, 2019)
Three-dimensional (3D) scaffolds formed from natural biopolymers gelatin and chitosan that are chemically modified by galactose have shown improved hepatocyte adhesion, spheroid geometry and functions of the hepatocytes. Galactose specifically binds to the hepatocytes via the asialoglycoprotein receptor (ASGPR) and an increase in galactose density further improves the hepatocyte proliferation and functions. In this work, we aimed to increase the galactose density within the biopolymeric scaffold by physically blending the biopolymers chitosan and gelatin with an amphiphlic beta-galactose polypeptide (PPO-GP). PPO-GP, is a di-block copolymer with PPO and beta-galactose polypeptide, exhibits lower critical solution temperature and is entrapped within the scaffold through hydrophobic interactions. The uniform distribution of PPO-GP within the scaffold was confirmed by fluorescence microscopy. SEM and mechanical testing of the hybrid scaffolds indicated pore size, inter connectivity and compression modulus similar to the scaffolds made from 100 % biopolymer. The presence of the PPO-GP on the surface of the scaffold was tested monitoring the interaction of an analogous mannose containing PPO-GP scaffold and the mannose binding lectin Con-A. In vitro cell culture experiments with HepG2 cells were performed on GLN-GP and CTS-GP and their cellular response was compared with GLN and CTS scaffolds for a period of seven days. Within three days of culture the Hep G2 cells formed multicellular spheroids on GLN-GP and CTS-GP more efficiently than on the GLN and CTS scaffolds. The multicellular spheroids were also found to infiltrate more in GLN-GP and CTS-GP scaffolds and able to maintain their round morphology as observed by live/dead and SEM imaging.
Keywords: adhesion; Aggregates; Cellular infiltration; Spheroids